Molecular docking and biochemical validation of (-)-syringaresinol-4-O-β-D-apiofuranosyl-(1→2)-β-D-glucopyranoside binding to an allosteric site in monoamine transporters - Liu, Hanhe; Wu, Yingyao; Li, Chan; Tang, Qingfa; Zhang, Yuan-Wei (Frontiers in Pharmacology, 2022)
Albizia julibrissin Durazz is one of the most common herbs used for depression and anxiety treatment, but its mechanism of action as an antidepressant or anxiolytic drug have not been fully understood. We previously isolated and identified one lignan glycoside compound from Albizia Julibrissin Durazz, (-)-syringaresinol-4-O-β-D-apiofuranosyl-(1→2)-β-D-glucopyranoside (SAG), that inhibited all three monoamine transporters with a mechanism of action different from that of the conventional antidepressants. In this study, we generated homology models for human dopamine transporter and human norepinephrine transporter, based on the X-ray structure of Drosophila dopamine transporter, and conducted the molecular docking of SAG to all three human monoamine transporters. Our computational results indicated that SAG binds to an allosteric site (S2) that has been demonstrated to be formed by an aromatic pocket positioned in the scaffold domain in the extracellular vestibule connected to the central site (S1) in these monoamine transporters. In addition, we demonstrated that SAG stabilizes a conformation of serotonin transporter with both the extracellular and cytoplasmic pathways closed. Furthermore, we performed mutagenesis of the residues in both the allosteric and orthosteric sites to biochemically validate SAG binding in all three monoamine transporters. Our results are consistent with the molecular docking calculation and support the association of SAG with the allosteric site. We expect that this herbal molecule could become a lead compound for the development of new therapeutic agents with a novel mechanism of action.